ALIH KODE DALAM PROGRAM â€œNEBENG BOY VLOG MUSIM 2â€ - Kaligis, Akiko Vicco Yuqio; Kodong, Fentje; Rattu, Jultje A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACT Â  Â  Â The title of this skripsi is â€œAlih Kode dalam Program â€œNebeng Boy Vlog Musim 2â€. The research uses descriptive method and analyzed from socilolinguistic point of view. The aims of this research are to identify, classify, and analyze the code switching appeared on â€œNebeng Boy Vlog Season 2â€ and to find the forms and reasons. This research uses the theory of Romaine (1995) to identify the forms and Hoffman (1991) for analyzed the reasons. The data were collected from 10 videos on â€œNebeng Boy Vlog Season 2â€ in Boy Williamâ€™s youtube channel. The total number of code switching are 205 data found in the conversation of Boy William and all his guests. The results of this research show that there are two types of code switching. They are inter-sentential code switching and intrasentential code switching. The results of this research show also that there are six reasons which influence the use of code switching on the program â€œNebeng Boy Vlog Season 2â€. They are talking about particular topic, quoting somebody else, showing emphatic (express solidarity), interjection (inserting sentence fillers or sentence connectors), making repetition used for clarification, and intention of clarifying the speech content for interlocutor.Keywords: Sociolinguistics, Code Switching, Nebeng Boy Vlog Season 2